Education reforms: consequences for the systems and the workers in education - Heleno Araújo Filho (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
This article approaches the consequences of the reforms in basic education, which started with the promulgation of the Federal Constitution of 1988. These reforms were elaborated without the social participation, resulting, nowadays, in high number of no literate people, big percentage of functional illiterates, the non universalization of the service school, low quality of the learning and a school with difficulties to accomplishing its paper of preparing the citizen for the life and the work. Besides, the education politics took a long time, after the Constitution, for being approved and they didn't assist to the claims and expectations of the workers' in education. However, in the last three years, there were changes in the structure of the Brazilian education, causing some progresses; but, still, there are challenges to be overcome. The author concluded getting the attention for the importance of the participation, organization and intervention of the organized entities of the social movements so that the present challenges in the education are overcome and that the education is in the right direction.